Rantai Nilai Cabai di Kawasan Lereng Gunung Merapi Daerah Istimewa Yogyakarta - Agus Dwi Nugroho; I Made Yoga Prasada; Saraswati Kirana putri; Herdiana Anggrasari; Pinjung Nawang Sari (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2020)
Fluctuation of the availability and prices of chili happen because the poor of the value chains. This research intended to know the mechanism related to the product, financial and information flow and development strategy to solve the problem of the chili’s value chain on the slopes of Mount Merapi. This research was conducted in Pakem District, Sleman Regency from May-August 2017. The method to determine the farmer respondents is random sampling while the merchants chosen by snowball sampling. The research used descriptive and SWOT analysis. The results showed that the most efficient marketing channels when farmers sell chili to the consumers through the retailers. Overall, the chili’s value chain included in the current category. Unfortunately, there are still some problems such as weak of the farmer cultivation ability and fluctuation of production and price. To solve this problem, the local government need make intensive counseling and training of chili cultivation, post-harvest handling in a professional and strengthen the auction market in Sleman Regency.